A description of psychosocial stressors of final year student nurses in a Private Training Facility in Gauteng - Freer, Karen Ann (My University, 2018)
Overall purpose of the study To identify the nature of the psychosocial stressors of final year student nurses in a private clinical training facility experience, with a view at a later stage of developing a preventive and support programme. Problem Statement Student nurses in the private training facility are subjected to many psychosocial stressors. Anecdotal evidence shows that these students are not coping with these stressors, as evidenced by attrition and mental health issues. The nature and extent of the stressors was not known. While confidential counselling service is available to students, this is a short term (maximum 6 sessions) service, and reactive in nature. By identifying common psychosocial stressors, an intervention to prevent or mitigate these stressors will, at a later stage, be developed. Research question What is the nature of psychosocial stressors that final year student nurses in the private clinical training facility experience? Research methods This was a qualitative research study using semi-structured interviews as a data collection tool. It was conducted in a private nursing education institution in Gauteng. Sixteen student nurses were interviewed and the data was analysed by means of a content analysis according to the steps of Braun and Clarke (2006). Major findings In this study, four categories of psychosocial stressors were identified viz. Academic pressure, financial constraints, work stress and social issues. The various stressors are interrelated. Academic pressure and financial constraints were the two most stressful issues for the student nurses. Conclusion Despite their obvious high levels of stress, the student nurses seem to be driven to complete their training despite overwhelming odds.
A research report submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Masters of Science. Johannesburg, 2018.
Keywords: Nurses; Stress, Psychological